Ñanananda’s Concept and Reality: An Assessment - Evans, Stephen (Buddhist Studies Review, 2017)
Bhikkhu Ñanananda’s Concept and Reality has exerted a certain influence on Buddhist Studies, from translations of the Pali Nikayas to interpretations of doctrine. Far beyond proposing translations for papañca and papañca-saññasankha, the book lays out a thesis, supported and illustrated by frequent citations from the Nikayas, concerning the role of concepts and language itself in perpetuating bondage to samsara. Concepts and language are said to obscure reality in a self-perpetuating cycle that bars us from liberation. The thesis has intuitive force and profound implications for understanding the Pali sources. However, the presentation is flawed by inconsistencies, lack of clarity, and overly interpretive translations of the Pali — it is not even clear in important details precisely what Ñanananda’s intended thesis is. The present offering is an attempt at clarifying this seminal work so as to enable building upon it. The given thesis is elucidated, making its problems explicit, and suggesting resolutions, arriving finally with a proposal of what he may have intended. Along the way, I indicate where given support from the Nikayas is weak.